2005
DOI: 10.1021/jo0502145
|View full text |Cite
|
Sign up to set email alerts
|

Highly Atom-Economic One-Pot Formation of Three Different C−P Bonds:  General Synthesis of Acyclic Tertiary Phosphine Sulfides

Abstract: The reaction of benzothiadiphosphole 1 with an equimolar mixture of R1MgBr and R2MgBr gave intermediate A', which, after only 4-5 min, was treated with an equimolar amount of R3MgBr, giving the asymmetric phosphine PR1R2R3 in 45% overall yield (75-80% yield when R1 = R2 and 85-90% yield when R1 = R2 = R3) and the byproduct 6 in 90% yield. The treatment of 6 with PCl3 quantitatively regenerates the starting reagent 1. Treatment of the phosphines with elemental sulfur gave the corresponding sulfides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Recently, we reported [5] (Scheme 1) a new synthesis of tertiary cyclic phosphanes 2 and 3 in 60-70 % yields [5a,b] by addition of a bisA C H T U N G T R E N N U N G (Grignard) reagent and a Grignard reagent to an unusual phosphorus-donor reagent, the benzothiadiphosphole 1 a, [6] called by us a "butterfly reagent" [7] owing to its particular folded structure. At the end of the reaction the starting reagent 1 a was quantitatively regenerated by addition of one equivalent amount of PCl 3 to the end-product 4, which is the remainder of 1 a obtained after quenching the reaction mixture with water (Scheme 1).…”
mentioning
confidence: 99%
“…Recently, we reported [5] (Scheme 1) a new synthesis of tertiary cyclic phosphanes 2 and 3 in 60-70 % yields [5a,b] by addition of a bisA C H T U N G T R E N N U N G (Grignard) reagent and a Grignard reagent to an unusual phosphorus-donor reagent, the benzothiadiphosphole 1 a, [6] called by us a "butterfly reagent" [7] owing to its particular folded structure. At the end of the reaction the starting reagent 1 a was quantitatively regenerated by addition of one equivalent amount of PCl 3 to the end-product 4, which is the remainder of 1 a obtained after quenching the reaction mixture with water (Scheme 1).…”
mentioning
confidence: 99%
“…For this purpose, we carried out the reaction between compound 1 and 3 equiv. of the Grignard reagent (as previously reported [25] to obtain acyclic tertiary phosphanes) and then we directly treated the reaction mixture containing the phosphanes 5a,b with BH 3 ·THF. In this manner, tertiary phosphaneborane complexes 6a,b were obtained in high yields (85-90 %) without isolation of the free phosphanes (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of such intermediates is favoured by the "dibenzo-butterfly" structure of 1, as we reported for the synthesis of cyclic tertiary phosphanes. [31] It is noteworthy that previously [25,31] we thought that the hexacoordinate intermediate AЈ required a nucleophilic attack, for example, by water or an acid in order to decompose it. During this study, however, we observed by 31 P NMR spectroscopy that AЈ is unstable and spontaneously collapses to give the corresponding tertiary phosphanes, presumably due to its high steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Achiral (R 3 P=O), prochiral (R 2 R 1 P=O) and chiral (R 1 R 2 R 3 P=O) phosphine oxides are the main precursors in the syntheses of corresponding phosphines, [1][2][3][4][5][6][7][8][9][10][11] which are widely used as ligands in metal complex catalysts 2,4,6,10,12 and neutral extracting agents for rare-earth metals. [13][14][15][16][17] Phosphine oxides can also be used as ligands in reactions catalysed by palladium and molybdenum complexes.…”
mentioning
confidence: 99%